4CPS-077 Do we need to adopt antifungal stewardship programmes? - Ioannidis, K (Eur J Hosp Pharm, 2018)
BACKGROUND: Although antimicrobial stewardship programmes are one of the highest priorities in healthcare systems, the appropriate use of antifungal agents has not been widely studied. Breakthrough infections from resistant Candida species have given rise to speculation over the deviation from the guidelines. PURPOSE: The aim of the present study is: To examine the distribution of Candida species. To observe a potential increase in the MICs of echinocandins and liposomal amphotericin–B. To assess the percentage of patients to whom antifungal treatment de–escalated after the identification of the susceptibility of the strain according to the guidelines of antifungal therapy. To calculate the financial cost, in those cases where the patient met the criteria to de–escalate therapy from echinocandins to fluconazole, or to continue therapy with fluconazole but they did not. MATERIAL AND METHODS: A retrospective analysis (2011 to 2016) of patients’ clinical data with confirmed candidaemia was performed. Data obtained from patients’ records, the microbiology laboratory and the pharmacy department. Patients were screened according to the following criteria: Patients aged above 18 years. Candidaemia confirmed with blood cultures positive for Candida spp. Empirical therapy with antifungal agent until culture results were obtained. Strain of Candida spp. susceptible to fluconazole. RESULTS: From the overall 157 patients with confirmed candidaemia (seven were excluded due to endocarditis) 58 received azoles, 74 echinocandins, 18 received liposomal amphotericin-B for empirical therapy. 51 patients were eligible to de-escatate to fluconazole but only 23 patients did so. Furthermore, nine patients from fluconazole re-escalated unjustified to echinocandins or liposomal amphotericin-B. The financial loss for the healthcare system due to the high prices of echinocandins and liposomal amphotericin B versus fluconazole, reached €211,836.29. Interestingly, it was found that one strain of C. albicans and two strains of C. glabrata were resistant to echinocandins. CONCLUSION: Our data indicate that empirical antifungal therapy is correct but regarding targeted antifungal therapy the de-escalation process is not implemented according to the guidelines. This leads to breakthrough infections from resistant Candida species and financial loss for healthcare systems because of the high cost of echinocandins and liposomal amphotericin-B. This raises the question concerning the necessity of adopting antifungal stewardship programmes in hospital settings. No conflict of interest